Bisnis Kreatif pada Usaha Rumah Tangga Kripik Tempe Sagu Mekar Jaya - Mujib Farkhan (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2023)
This study aim For know How business creatively done on business House ladder chips tempeh sago blossom triumph. Entrepreneurship is ability creative, jelly see opportunity And always open For every input And positive changes that can bring business Keep going grow. This research uses a qualitative approach with data from home-based business actors who belong to the Mekar Jaya Trenggalek chips business group. With many activity existing business moment This of course requires entrepreneurs to always develop new ideas. Of course his business creative become something always thing walk side by side inside world business mainly For maintain moderate business run